Isolasi dan Elusidasi Struktur Senyawa Flavonoida Dari Crotalaria anagyroides - Munim, Abdul (UI Scholars Hub, 2005)
Four flavonoid glycosides have been isolated from the leaves of Crotalaria anagyroides. The glycosides are 1) apigenin 7-O-β-D-apiofuranosyl (1!6)-β-glucopyranosida, 2) apigenin 7-O-β-D-apiofuranosyl (1!2)-β-glucopyranoside, 3) chrysoeriol 7-O-β-D-apiofuranosyl (1!6)-β-D-glucopyranoside, 4) chrysoeriol 7-O-β-D-apiofuranosil (1!2)-β-D-glucopyranoside. Their structures were elucidated by spectroscopic methods of UV, 1H, 13C and 2D-NMR DEPT, COSY and HMBC experiments.